Lithium battery lodged in the oesophagus: A report of three paediatric cases. Issue 11 (November 2015) - Barabino, Arrigo Vittorio; Gandullia, Paolo; Vignola, Silvia; Arrigo, Serena; Zannini, Lucio; Di Pietro, Pasquale
Abstract Background Over the last years the ingestion of disk batteries has become frequent in children with serious consequences. The severity of injuries is related to the growing use of new lithium batteries that may cause catastrophic damages when lodged in the oesophagus. Methods The notes of three consecutive children with lithium batteries lodged in the oesophagus, admitted to our Institute from 2010 to 2014, were reviewed. Clinical presentation, management, and outcome were considered. Results The first child, a 22-month-old girl, died of a sudden exsanguination due to an aorto-oesophageal fistula. The second case, a 5-year-old boy, had an exploratory thoracotomy to exclude aortic lesion before battery removal, and a spontaneous oesophageal perforation. The third child, a 18-month-old boy, fully recovered after suffering ulcerative oesophageal burns. Conclusion Lithium battery lodged in the oesophagus is a paediatric emergency requiring a multidisciplinary approach that can be implemented in a tertiary children's hospital.